Proyecto de factibilidad para la creación de una microempresa de servicios mecánicos de alineación y balanceo en el cantón Lago Agrio, provincia de Sucumbíos - Moncayo Reyes, Jessica Daniela (2016)
This thesis will reveal the viability for the creation of a micro-mechanical alignment and balancing services in Cantón Lago Agrio, Sucumbíos Province. Once all the necessary information was obtained for the project feasibility, using methods and techniques such as inductive, deductive, descriptive, analytical method and survey techniques and direct observation. Has developed a market study by which it was determined an extensive unmet demand, data obtained by applying and 381 surveys were obtained data having applied the relevant formulas to determine the economically active population. The technical study which yielded information resources, materials, equipment, location, size, distribution, viability and feasibility to implement microenterprise was performed. Within this technical study location microenterprise determined as an ideal location at Km 6 ½ Quito Road place analyzed; which it is considered as a strategic and commercial point. Within the administrative study it found that microenterprise SA will also proceeded to develop the structural and functional organization, with its own manual functions. The study found financial indicators such as VAN to $ 2248.01 USD United States of America and the TIR is 11.86%. Economic indicators established by recovery period of three years demonstrated the feasibility and viability of this project. Microenterprise will be directed to service alignment and balancing, which is why we use tech machinery which will facilitate the provision of mechanical services with excellent quality. This service is aimed at automotive owners, residents, who wish to service alignment and balancing tires quickly, safely, using specific machinery for each service.